Metabolite profiling by UPLC-PDA-ESI/HDMS and antibacterial activity of Memecylon talbotianum Brandis - Bharathi, Tumkur Ramasetty; Sekhar, Shailasree; Kumara, Kigga Kadappa Sampath; Madhusudhan, Mudalabeedu Chandregowda; Prakash, Harishchandra Sripathy (Pharmacognosy Communications)
Introduction: UPLC based metabolite profiling was employed to evaluate the chemical constituents of Memecylon talbotianum Brandis extract and its antibacterial activity was studied in vitro. Methods: Methanol extracts of M. talbotianum was subjected to UPLC-PDA-ESI/HDMS metabolite profiling. The antibacterial activity was determined against human pathogens through disc diffusion, Minimum inhibitory concentration (MIC), Minimum biofilm inhibitory concentration (MBIC) test as visualized by Alamar blue and confocal laser scanning microscopy. Results: UPLC-PDA-ESI/HDMS analysis identified eighteen metabolites, synapoyl-hexose-formic acid, kaempferol 3-O-feruloylhexosyl rhamnoside, 6-C-arabinosyl-8-C-glucosyl- apigenin and isorhamnetin-3-O-glycoside-7-O-glycoside as the main con- stituents for the first time from this plant. A broad spectrum of antibacterial activity against to test human pathogens (MIC=54 mg/ mL; Gram-positive bacteria) causing lysis at 24 h incubation was reported, resulting in nearly a 4 log10 CFU / mL drop in cell viability at 1.6 X MIC (Gram-positive) for this extract. The extract at 2 fold MIC inhibited the bacterial biofilm formation and at 8 x MIC eradicated biofilms. However, a higher concentration of this extract was identified in this study for a similar effect on Gram-negative bacteria. Conclusion: The presence of these compounds could contribute to their in vitro inhibitory activities against pathogenic bacterial strains indicating its potential as medicinal agents in treatment and prevention of diseases of bacterial origin.
Keywords: UPLC-PDA-ESI/HDMS; Bioactives; Anti-bacterial activity; Biofilm; MIC.